2020
DOI: 10.1016/j.semperi.2020.151276
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of health professions students during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has posed challenges for medical education and patient care, which were felt acutely in obstetrics due to the essential nature of pregnancy care. The mobilization of health professions students to participate in obstetric service-learning projects has allowed for continued learning and professional identify formation while also providing a motivated, available, and skilled volunteer cohort to staff important projects for obstetric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with the absence of psychological support reported by over 60% of the respondents, this indicates that insufficient care was taken to ensure volunteers' well-being. Well-being assistance does not always require substantial institutional outlays: it can be provided by volunteers themselves, as it happened at the Columbia University in the USA ( 11 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Poznań project seems to be among the few interprofessional COVID-19 SVPs described in the latest literature, partly due to the fact that some medical schools offer only medical programmes. A large-scale multidisciplinary SVP was initiated by the Columbia University Irving Medical Center in New York, USA; it soon turned into a national initiative ( 11 , 18 ). The project website stresses that collaboration should be interprofessional “to promote students learning with, from, and about each other through their service” ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations